Synthesis of a novel analog of calcitriol and its biological evaluation as antitumor agent - Ferronato, María Julia (2019)
Calcitriol analogs have shown promising potential as compounds to be used in cancer chemotherapy. This report presents the synthesis of a novel vitamin D3 derivative with an amide and a carboxyl group in its side chain, called ML-344. In addition, we report its in vitro antitumor activity and its in vivo calcemic effects. We demonstrate that the analog decreases cell viability and retards cell migration of different breast, glioblastoma and head and neck cancer cell lines. Additionally, unlike calcitriol, ML-344 does not display citotoxicity to the murine non-malignant mammary cells and human astrocytes. In concordance with the antimigratory effects found in breast cancer cells, ML-344 decreased the invasive capacity and induced a rearrangement of the actin cytoskeleton in the LM3 breast cancer cell line. In relation to the in vivo studies, the analog did not cause hypercalcemic effects in CF1 mice administered daily at 5 μg/Kg of body weight during a period of 264 h. Finally, computational studies were performed to evaluate the potential binding of the analog to the vitamin D receptor and the in silico assays showed that ML-344 is able to bind to VDR with interesting particularities and greater affinity than calcitriol. Altogether, these results suggest that ML-344 has a promising potential as an antitumor agent with a differential effect between tumor and non-malignant cells.